New method to evaluate three-dimensional push-off angle during short-track speed skating using wearable inertial measurement unit sensors - Kim, K.; Kim, J. S.; Purevsuren, T.; Khuyagbaatar, B.; Lee, S.; Kim, Y. H. (Journal of Engineering in Medicine, 2019)
The push-off mechanism to generate forward movement in skating has been analyzed by using high-speed cameras and specially designed skates because it is closely related to skater performance. However, using high-speed cameras for such an investigation, it is hard to measure the three-dimensional push-off force, and a skate with strain gauges is difficult to implement in the real competitions. In this study, we provided a new method to evaluate the three-dimensional push-off angle in short-track speed skating based on motion analysis using a wearable motion analysis system with inertial measurement unit sensors to avoid using a special skate or specific equipment insert into the skate for measurement of push-off force. The estimated push-off angle based on motion analysis data was very close to that based on push-off force with a small root mean square difference less than 6% when using the lateral marker in the left leg and the medial marker in the right leg regardless of skating phase. These results indicated that the push-off angle estimation based on motion analysis data using a wearable motion capture system of inertial measurement unit sensors could be acceptable for realistic situations. The proposed method was shown to be feasible during short-track speed skating. This study is meaningful because it can provide a more acceptable push-off angle estimation in real competitive situations.